Water Quality Index (WQI) of Jaguari and Atibaia Rivers in the region of Paulínia, São Paulo, Brazil - Ramos, Marcio Antonio Gomes [UNESP]; Bueno de Oliveira, Eduardo Schneider [UNESP]; Pião, Antonio Carlos Simões [UNESP]; Nalin de Oliveira Leite, Dilza Aparecida [UNESP]; de Franceschi de Angelis, Dejanira [UNESP] (Springer Nature, 2016)
Due to the concern with the quality of hydric resources, the monitoring is essential to evaluate and identify the anthropogenic and environmental interferences in a quantitative and qualitative level. In order to assist the interpretation of the water status of hydric bodies, the gathering of analytical data often considers the Water Quality Index (WQI). This index transforms technical information in description of the water quality status, highlighting the effectiveness of its use and guiding the decision-making process when necessary. The aim of this research is to assess the water quality of a region in São Paulo State, Brazil, by means of the WQI of Jaguari and Atibaia Rivers. The period of intense drought, which affected the Brazilian southeast in 2014, was evaluated and compared to the mean values recorded from October 2009 to March 2015, correlating the values of Escherichia coli and the biochemical oxygen demand (BOD). One hundred nine samples were collected, being 53 from dry seasons, between October and March, and 56 from rainy seasons, between April and September. The WQIs in Jaguari and Atibaia Rivers, during dry season, were of 42.2 (medium) and 36.7 (bad), respectively. The same pattern was registered for the dry season, for both rivers, with indices values of 40.1 for Jaguari River (medium) and 34.9 for Atibaia River (bad). This research presented the need of an effective evaluation of the environmental quality and preservation by competent organs for both rivers. Due to the detected conditions, special attention should be given to the Atibaia River.
Keywords: Atibaia River; Biochemical oxygen demand; Escherichia coli; Jaguari River; Water quality index